Surgical malpractice claims in the United States. Issue 4 (April 2014) - Jiam, Nicole Tin‐Lok; Cooper, Michol A.; Lyu, Heather G.; Hirose, Kenzo; Makary, Martin A.
<x xml:space="preserve">Abstract</x> Despite ongoing reform, there is still significant physician concern regarding the impact of medical claims on their practices. It is important that physicians and healthcare risk management professionals have a good understanding of the outcomes of medical malpractice to participate in its restructuring as needed and to prevent potentially harmful practices. In our study, we reviewed National Practitioner Data Bank (NPDB) paid malpractice claim reports from September 1, 1990, through July 30, 2011, and identified the 10 most common surgery‐related allegations against physicians, excluding those listed as unspecified. Data were collected on the number of claims, the cost of the claims, and physician and patient characteristics.